Chaetomitrium Borneense - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Branches tumid with spirally arranged leaves; (2) stem leaves are imbricate-patent, broadly incurved above, deeply concave, ovate-oblong when flattened with cuspidate apices; (3) leaf margins are minutely denticulate with simple teeth; (4) lamina cells are prorulate, becoming more incrassate and shorter near apices; (5) lamina cells of branch leaves are more prorate than those of stem leaves; (6) calyptrae (immature) are small, mitriform, with long cilia at the base.